Hydroponic Salinity Screening by Deep Flow Technique on All Paddy Growing Phases - N. Nasaruddin; Muhammad Fuad Anshori; Muh. Farid BDR; Hari Iswoyo; Yunus Musa; Muh. Arifuddin; Andi Isti Sakinah (Universitas Sembilanbelas November Kolaka, 2021)
Salinity screening under hydroponic Deep Flow Technique (DFT) has not been widely studied, especially on the nature of rice tolerance to salinity stress. According to previous screening studies, this method was effective in distinguishing the nature of rice tolerance to salinity stress. However, they were tested only at generative phase. Therefore, evaluation on screening method with hydroponic DFT at all phases of paddy growth is essential. The objective of this study is to evaluate the filtering under hydroponic DFT at all paddy phase and to determine secondary character that support productivity which can be utilized as selection character in this screening process. The experiment was arranged with a complete nested group design with nested replication is the NaCl stress. There were 5 (Five) tested rice varieties and the stress environment consisted of three levels: 0, 60, and 120 mM of NaCl, all with 3 (three) replications. The nutrient culture screening was adapted to the modified Egdane method. The results showed that screening under hydroponic DFT was effective at the concentration of 60 nM of NaCl. The best selection character was yields per clump, number of productive tillers and total chlorophyll. The variety of Jeliteng, Ciherang and Inpari 34 of Salin Agritan, were classified as tolerant group. This hydroponic DFT Filtering method could be recommended as one salinity screening method for all paddy growing phases